The Effect of Hole Variation on The Performance of Catalytic Conventer from Pulp Waste with Zeolit X Catalyst from Rice Husk Ash - Iis Siti Jahro; Moondra Zubir; Jasmidi; Putri Faradilla; Banu Nursanni; Tania Evelin (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
The use of a catalytic converter in the exhaust is one solution to reduce pollutant levels in motor vehicle gas emissions. The catalytic converter was made using pulp waste and zeolite X from rice husk ash. This research examines the effect of varying number of holes 3, 5 and 7 on the absorption and conversion capacity of the catalytic converter. Making a catalytic converter from solid pulp waste consisting of grit, dreg and biosludge with the addition of zeolite synthesized from rice husk ash is carried out through the stages of granulating, mixing, molding and burning. The performance of the catalytic converter is measured using the Gas Analyzer shows that the catalytic converter with the 7 holes has the maximum absorption capacity for each motor vehicle gas emissions; CO, HC and CO2 respectively amounted to 39.06; 33.18 and 44.80% with an increase in O2 gas of 42.21%.